How Useful Is Endoscopic Ultrasound in Differentiating T3/T4a T Stage of Colorectal Cancer: A Prospective Study - Han, Chaoqun; Tang, Xuelian; Yang, Ming; Zhang, Kun; Liu, Jun; Lin, Rong; Ding, Zhen (Frontiers in Oncology, 2022)
Objective Endoscopic ultrasound (EUS) is an established method for staging of colorectal cancer. Nevertheless, prior assessments of its T stage accuracy have been limited, particularly ambiguity in assessed T3 and T4a stage. This study was to characterize the EUS image features and pay attention to distinguish T3 from T4a T stage. Methods A total of 638 patients who prospectively underwent colorectal EUS were recorded. The final diagnoses were compared with the concurrent or follow-up histopathology. Univariate and multivariate logistic regressions were used to assess variation in diagnostic performance with case attributes. Results The accuracies of EUS in classifying colorectal cancer for overall, T1, T2, T3, and T4a stages are 73.04, 62.32, 67.46, 71.26, and 83.52%, respectively. With attention to EUS image features, the lesion penetrates the entire wall and locates below the seminal vesicles or cervix is T3 stage. If the lesion locates above clearly-defined space between the anterior rectal wall and the posterior surface of the seminal vesicles or cervix, we identify as T4a stage; However, when located above seminal vesicles or cervix but on the posterior wall of the rectum, the lesion still considers as T3 stage. The tumor location and histological type are associated with inaccuracy T stage. Conclusions EUS provides reliable diagnostic accuracy in the colorectal cancer stage. The seminal vesicles and cervix are the important markers to predict infiltration depth for T3/T4a stage. Furthermore, the tumor location, histological type, and EUS image features for each tumor T stage should warrant attention.